2019
DOI: 10.1111/jfpe.13030
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage and rehydration characteristics of vacuum assisted microwave dried green bell pepper

Abstract: Green bell pepper was dried under vacuum assisted microwave (VAM) drying conditions. The effect of microwave power (100, 200, 300 W) and vacuum pressure (200, 400, 600 mmHg) were observed on shrinkage and rehydration characteristics of the sample. Shrinkage was modeled as a linear function of volume change of material and its moisture content. A model was proposed where apparent density could be evaluated as a function of product's moisture content. The sample volume in case of VAM drying shrunk by 59 to 78%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Therefore, the simulation results of the radial and axial displacements matched well with the experimental data. Moreover, the deformation rates are also given in Figure 5, which indicates that the deformation rate reached the global maximum around 600 s due to the collapse of cell structure caused by moisture loss [56]. Moreover, the coefficients of determination and the root mean square errors of the two models were R 2 = 0.437 and R 2 = 0.345, and RMSE = 13.5 • C and RMSE = 15.4 • C, respectively.…”
Section: Deformation Displacementsmentioning
confidence: 89%
“…Therefore, the simulation results of the radial and axial displacements matched well with the experimental data. Moreover, the deformation rates are also given in Figure 5, which indicates that the deformation rate reached the global maximum around 600 s due to the collapse of cell structure caused by moisture loss [56]. Moreover, the coefficients of determination and the root mean square errors of the two models were R 2 = 0.437 and R 2 = 0.345, and RMSE = 13.5 • C and RMSE = 15.4 • C, respectively.…”
Section: Deformation Displacementsmentioning
confidence: 89%
“…The appropriate drying method, especially for sensitive biological products such as green pepper, is important for both the quality of the dried product and the expenses of the process (Mahanti et al, 2021). Vacuum-assisted microwave drying (Kumar et al, 2019;Kumar and Shrivastava, 2017), heat pump-assisted fluidized bed drying (Jafari et al, 2016), IR-assisted spouted bed dryer (Moradi et al, 2020) and osmotic drying (Odewole et al, 2016) are recent studies on green pepper. No study was found on Maraş green pepper in the literature review.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation constants and ANOVA of the linear model representing the volumetric shrinkage at various drying conditions(Mazza and Lemaguer, 1980;Kumar et al, 2019) …”
mentioning
confidence: 99%